find the value of a when g(x) is a factor of p(x).
1. g(x) =x+1; p(x)=x power 2 +ax+2.
Answers
Answered by
3
here , g(x) = x + 1
=> x + 1 = 0
=> x = -1
if g(x) is a factor of P(x) , then
p(-1) = 0
p(x) = x² + ax + 2
=> p(-1) = (-1)² + a(-1) + 2
=> 0 = 1 + 2 - a
=> a = 3
The value of a is 3 .
....
...
..
.
Answered by
10
find the value of a , when g(x) is a factor of p(x).
1. g(x) =x+1;
![p(x) = {x}^{2} + ax + 2 \\ \\ p(x) = {x}^{2} + ax + 2 \\ \\](https://tex.z-dn.net/?f=p%28x%29+%3D+%7Bx%7D%5E%7B2%7D+%2B+ax+%2B+2+%5C%5C+%5C%5C+)
As we know that if g(x) is a factor polynomial of p(x) then by factor theorem it must satisfies the polynomial p(x).
Calculate value of x,by g(x)
![g(x) = x + 1 \\ \\ x + 1 = 0 \\ \\ x = - 1 \\ \\ g(x) = x + 1 \\ \\ x + 1 = 0 \\ \\ x = - 1 \\ \\](https://tex.z-dn.net/?f=g%28x%29+%3D+x+%2B+1+%5C%5C+%5C%5C+x+%2B+1+%3D+0+%5C%5C+%5C%5C+x+%3D+-+1+%5C%5C+%5C%5C+)
Find P(-1)
![p( - 1) = 0\\ \\ p( - 1) = ( { - 1)}^{2} + a(-1) + 2 \\ \\ 1 - a + 2 = 0 \\ \\ -a + 3 = 0 \\ \\ -a = - 3 \\ \\a=3\\\\ p( - 1) = 0\\ \\ p( - 1) = ( { - 1)}^{2} + a(-1) + 2 \\ \\ 1 - a + 2 = 0 \\ \\ -a + 3 = 0 \\ \\ -a = - 3 \\ \\a=3\\\\](https://tex.z-dn.net/?f=+p%28+-+1%29+%3D+0%5C%5C+%5C%5C+p%28+-+1%29+%3D+%28+%7B+-+1%29%7D%5E%7B2%7D+%2B+a%28-1%29+%2B+2+%5C%5C+%5C%5C+1+-+a+%2B+2+%3D+0+%5C%5C+%5C%5C+-a+%2B+3+%3D+0+%5C%5C+%5C%5C+-a+%3D+-+3+%5C%5C+%5C%5Ca%3D3%5C%5C%5C%5C+)
Hope it helps you
1. g(x) =x+1;
As we know that if g(x) is a factor polynomial of p(x) then by factor theorem it must satisfies the polynomial p(x).
Calculate value of x,by g(x)
Find P(-1)
Hope it helps you
Similar questions